Pogledi Jožeta Rajhmana na slovensko zgodovino 19. in 20. stoletja - Maver, Aleš (Edinost in dialog, 2025)
Rajhman's encounters with the history of Slovenian areas between (roughly) 1800 and 1950 could be quickly classified into a few compartments. Most important for his understanding of Jernej Kopitar is the essay on the relationship between Austro-Slavism and Catholicism by the Viennese court librarian. Here one is at least a little surprised by the caustic assessment of Kopitar's religious zeal. In regards to the activities of the Slovene Protestants in the 16th century as a nexus of the culture wars among the Slovenes at the turn of the 19th to the 20th century, Rajhman is most impressed by Ivan Prijatelj's assessment in a text from 1908. The article Slovene “Nationalism and Christianity” is very important. In it, the theologian clearly outlines the development of views on the hierarchy of values on the question of the nation in Slovenian Catholic thought in the 19th and 20th centuries. With his understanding of Slovenia's past and especially of the decisive turning points of the 19th and 20th centuries, Rajhman clearly fits into that stream of Catholic thought in Slovenia which was able to retain at least a modicum of voice in the public sphere after the Second World War.
Keywords: culture wars; Kopitar, Jernej; kulturni boj; Rajhman, Jože; religion and nation; Slovenian history of the 19th and 20th centuries; slovenska zgodovina 19. in 20. stoletja; vera in narodnost